A time‐to‐event model for acute rejections in paediatric renal transplant recipients treated with ciclosporin A. (24th September 2013) - Frobel, Anne‐Kristina; Karlsson, Mats O.; Backman, Janne T.; Hoppu, Kalle; Qvist, Erik; Seikku, Paula; Jalanko, Hannu; Holmberg, Christer; Keizer, Ron J.; Fanta, Samuel; Jönsson, Siv
Abstract : Aims: Ciclosporin A (CsA) dosing in immunosuppression after paediatric kidney transplantation remains challenging, and appropriate target CsA exposures (AUCs) are controversial. This study aimed to develop a time‐to‐first‐acute rejection (AR) model and to explore predictive factors for therapy outcome. Methods: Patient records at the Children's Hospital in Helsinki, Finland, were analysed. A parametric survival model in NONMEM was used to describe the time to first AR. The influences of AUC and other covariates were explored using stepwise covariate modelling, bootstrap‐stepwise covariate modelling and cross‐validated stepwise covariate modelling. The clinical relevance of the effects was assessed with the time at which 90% of the patients were AR free ( t 90 ). Results: Data from 87 patients (0.7–19.8 years old, 54 experiencing an AR) were analysed. The baseline hazard was described with a function changing in steps over time. No statistically significant covariate effects were identified, a finding substantiated by all methods used. Thus, within the observed AUC range (90% interval 1.13–8.40 h mg l −1 ), a rise in AUC was not found to increase protection from AR. Dialysis time, sex and baseline weight were potential covariates, but the predicted clinical relevance of their effects was low. For the strongest covariate, dialysis time, median t 90 was 5.8 days (90% confidence interval 5.1–6.8) for long dialysis times (90th percentile) and 7.4 days (6.4–11.7) for short dialysis times (10th percentile). Conclusions: A survival model with discrete time‐varying hazards described the data. Within the observed range, AUC was not identified as a covariate. This feedback on clinical practice may help to avoid unnecessarily high CsA dosing in children.